EMOTIONAL INTELLIGENCE AND DIGITAL LITERACY ON PROFESSIONAL COMPETENCE OF BASIC EDUCATION TEACHER (Proceedings of the International Conference on Future of Education, 2023)
The digitization of instructional delivery is caused by the global pandemic, consequently, numerous challenges were encountered by teachers on the use of digital technology in the instructional processes.  Hence, this conceptualizes the study of teachers' professional competence, digital literacy, and emotional intelligence.  The study involved 300 basic education teachers from three Districts of Maramag school year 2022-2023.  This study utilized descriptive-correlational design to determine the relationship between emotional intelligence and digital literacy on professional competence.  The study found that teachers exhibited emotional intelligence most of the time, it is indicated that they know how to handle their emotions and feelings and manage the emotions of others.  Similarly, teachers had a high level of digital literacy, this implies that they had knowledge and skills in technology operations and pedagogical competence since they utilize digital technologies and tools in their teaching practice, specifically, technology operation and pedagogical competence. Finally, teachers denote high professional competence, including planning, development, and teaching-result. The results showed that emotional intelligence and digital literacy had a significant relationship with teachers' professional competence. Among the sub-variables, social skills, technological operations, and concepts had the highest mean, indicating that teachers exhibited these emotions and were highly literate in digital technology. Self-awareness, motivation, managing emotions, social skills, and technological operations and concepts were found predictors of teachers' professional competence.  The findings highlight the significance of emotional intelligence and digital literacy for the professional competence professional competent basic education teachers. Teachers who exhibited high levels of emotional intelligence and digital literacy were more competent in the classroom, while the students experienced positive learning outcomes.
Keywords: emotional intelligence; digital literacy; professional competence; basic education teachers